Four Novel Screw-like Tris(1,10-phenanthroline) Ruthenium(II) Bishexafluorophosphate Derivatives - Wang Guoyi Zhu, Peng (Asian Journal of Chemistry, 2010)
Four novel screw-like Ru(II) complexes, tris(5-lauramide-1, 10-phenanthroline) Ru(II) bishexafluorophosephate, tris(5-myristamide-1,10-phenanthroline)Ru(II) bishexafluorophosphate, tris(5-palmitamide-1,10-phenanthroline)Ru(II) bishexafluorophosphate and tris (5-stearamide-1,10-phenanthroline )Ru(II) bishexafluorophosphate have been efficiently synthesized. They are confirmed by the techniques of IR, 1H NMR, 1H-1H COSY and ES-MS. Also, their electrochemistry, fluorescence and electrochemiluminescence are reported.